PSYCHOLOGICAL WELL-BEING DAN MOTIVASI BELAJAR MAHASISWA - Yapputro , Nikole Edmonda; Angelina , Cindy; Virenna , Rachel; Pranata, Reni Juniarsa; Aurelia , Verena; Wijaya , Erik (Fakultas Psikologi Universitas Tarumanagara, 2025)
Quality education can affect motivation for learning. One of the factors that influences motivation in learning is psychological well-being (PWB). Some previous research found that there are differences in results between PWB and learning motivation when viewed from gender. Therefore, this study was conducted to know the relationship between psychological well-being and student learning motivation, as well as the description of PWB and learning motivation when viewed from gender. This research is processed with a quantitative approach. The participants selected in the study were 400 Tarumanagara University students aged 18-21 years. Data collection was done using a questionnaire. The results of this study show that there is a positive and significant relationship between PWB and students' learning motivation (r = 0.676, p < 0.01); and there is no significant difference in learning motivation and PWB when viewed from gender. Thus, this study is expected to help students to better understand the importance of PWB in increasing their learning motivation.